Implementation of the Advanced Encryption Standard (AES) Algorithm to Protect Children Personal Data - Patty, Dyana; Dahoklory, Novita; Kololu, Selvy Marchia; Leleury, Zeth Arthur (Parameter: Jurnal Matematika, Statistika dan Terapannya, 2025)
The rapid development of information and communication technology is inseparable from data security issues. In today's digital age, one type of data that is vulnerable to cyber security threats is children's personal data. Protecting children's personal data is an important priority in safeguarding their privacy and digital security. This research applies AES-256 on a website to secure personal data within the database. AES-256 is a symmetric cryptographic and block-ciphertext algorithm that can encrypt and decrypt data/information with a key size of 256 bits, which can be used to secure data. Results demonstrate that AES-256 effectively maintains full name, NIK and password confidentiality and integrity, rendering the encrypted ciphertext difficult to interpret or access. This study provides a basis for advancing data security and related applications which strengthens the complexity of encrypted children's personal data against cryptanalysis attacks.